Cesarean section and the gestational duration of subsequent pregnancies: A nationwide register-based cohort study - Felix Evers; Christopher Flatley; Karin Ytterberg; Julius Juodakis; Pol Solé-Navais; Bo Jacobsson (PLoS ONE, 2025)
Introduction Preterm delivery risk is increased for women with a previous cesarean section, which are becoming more common worldwide. However, this risk is based on studies which have not fully accounted for selection bias, and the studied outcomes have been limited to the study of early deliveries. This study aimed to determine the impact of previous delivery modes on the incidence of deviant duration of subsequent pregnancies. Material and methods This retrospective cohort study used clinical data registered in the Swedish Medical Birth Register. 612 935 women with their first two pregnancies and 157 581 women with their first three pregnancies were included. The outcome was the gestational duration of the last pregnancy of the series, depending on previous delivery modes. The associations were analysed with multivariable logistic regression (with the gestational duration categorised) and survival models including Cox regression analyses. Results When using standard logistic regression, previous cesarean section was associated with an increased risk of both spontaneous preterm birth (adjusted odds ratio [aOR] 1.67, 95% CI 1.57–1.77) and postterm birth (aOR 1.55, 95% CI 1.49–1.62). However, the more appropriate survival models only showed an association between cesarean section and longer gestational duration of the subsequent pregnancy (adjusted hazard ratio 0.72, 95% CI 0.71–0.73). Conclusions The survival model handles bias related to management differences between the exposure and reference groups better than standard logistic regression, making it the statistical method of choice when conducting studies on this research topic. This study shows that the main association between cesarean section and the gestational duration of the subsequent pregnancy is the prolonging of it, which stands in contrast with previous research on the topic.